2019
DOI: 10.30596/jimb.v20i1.2397
|View full text |Cite
|
Sign up to set email alerts
|

Meningkatkan Kinerja Pemasaran melalui Orientasi Pasar dan Orientasi Kewirausahaan

Abstract: Penelitian ini menganalisis pengaruh orientasi pasar dan orientasi kewirausahaan terhadap kinerja pemasaran Usaha Mikro Kecil Menengah (UMKM) kuliner di Ciganjur, Jakarta Selatan. Adapun tujuan dari penelitian ini dilakukan untuk: (1) menentukan pengaruh dari orientasi pasar terhadap kinerja pemasaran (2) menentukan pengaruh dari orientasi wirausaha terhadap kinerja pemasaran. Dengan menggunakan pendekatan penelitian deskriptif kuantitatif, teknik pengambilan sampel yang digunakan dalam penelitian ini adalah m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 1 publication
2
9
0
5
Order By: Relevance
“…If entrepreneurial orientation was experienced, the marketing performance did not experience the same increase in home furniture industry in Sawahan District. The results of this study support the research conducted by Aulia et al, (2019), Hatta (2015, and Setyawati (2013), which stated that entrepreneurial orientation has no significant effect on marketing performance, so it can be understood that this study can strengthen the results of previous researches. In a study conducted by Setyawati (2013), the entrepreneurial orientation variable is an antecedent of market orientation, so that it affects the outcome of the relationship that is not significant.…”
Section: The Effect Of Entrepreneurship Orientation (X 1 ) On Marketing Performance (Y)supporting
confidence: 87%
See 2 more Smart Citations
“…If entrepreneurial orientation was experienced, the marketing performance did not experience the same increase in home furniture industry in Sawahan District. The results of this study support the research conducted by Aulia et al, (2019), Hatta (2015, and Setyawati (2013), which stated that entrepreneurial orientation has no significant effect on marketing performance, so it can be understood that this study can strengthen the results of previous researches. In a study conducted by Setyawati (2013), the entrepreneurial orientation variable is an antecedent of market orientation, so that it affects the outcome of the relationship that is not significant.…”
Section: The Effect Of Entrepreneurship Orientation (X 1 ) On Marketing Performance (Y)supporting
confidence: 87%
“…The results of research conducted by Buli (2017) and Masa'deh et al (2018) show that entrepreneurial orientation has a positive and significant effect on marketing performance. Entrepreneurial orientation as a process, practice, and decision-making skill that reflected in directing companies to engage in innovative, proactive, and risk-taking behavior in order to improve company performance (Aulia et al, 2019). The results of the study by Aulia et al (2019) showed that entrepreneurial orientation did not significantly influence marketing performance.…”
Section: Development Of Hypothesismentioning
confidence: 99%
See 1 more Smart Citation
“…Orientasi pasar merupakan salah satu faktor yang bisa membawa pada meningkatnya kinerja pemasaran (Aulia et al, 2019). Orientasi pasar adalah kondisi dimana sebuah perusahaan dalam melakukan suatu keputusan berdasarkan kondisi riil di pasar dan melakukan pendekatan -pendekatan pada pasar dengan cara penelitian dan memahami nilai-nilai yang berlaku (Pertiwi & Siswoyo, 2016).…”
Section: Pendahuluanunclassified
“…Penelitian sebelumnya menyatakan bahwa perusahaan dituntut untuk melakukan sebuah inovasi yang dapat menyempurnakan dan mengembangkan suatu produk untuk mempertahankan kelangsungan hidup dan keuntungan perusahaan (Rizki, 2019). Perusahaan yang berorientasi pada kewirausahaan akan melakukan inovasi yang kreatif, proaktif, dan berani mengambil resiko, maka dengan begitu perusahaan akan lebih maju karena selalu melakukan perbaikan (Pureati et al, 2021) Dapat disimpulkan dari pengertian diatas bahwa inovasi adalah seseuatu kreatifitas untuk merubah suatu produk ataupun jasa yang memiiki nilai lebih dan memiliki perbedaan dari para pesaingnya.…”
unclassified